Predictive Value of the HEART Score Combined with Hypersensitive C-Reactive Protein for 30 d Adverse Cardiovascular Events in Patients with Acute Chest Pain - Maosheng Lin; Louwei Zhang; Xuhua Tang; Yejiang Tang (Emergency Medicine International)
Purpose. This study aimed to explore the predictive value of the HEART score combined with hypersensitive C-reactive protein (hs-CRP) for 30 d major adverse cardiovascular events (MACEs) in patients with acute chest pain. Methods. 103 patients with acute chest pain admitted to the emergency department of our hospital from May 2020 to May 2022 were selected as the study subjects. The patients’ HEART score and plasma hs-CRP level were recorded. The patients were followed up for 30 d to observe whether MACE occurred. Results. Among 103 patients with acute chest pain, MACE occurred in 8 cases within 30 d of follow-up, and the probability of MACE was 7.76%. There was a statistically significant difference in 30 d MACE risk among patients with different HEART score stratification (P<0.05). The age, HEART score, and hs-CRP levels of patients in the MACE group were higher than those in the non-MACE group (P<0.05). The HEART score and the hs-CRP level were independent risk factors for 30 d MACE in patients with acute chest pain (P<0.05). The AUC of the HEART score combined with hs-CRP in the occurrence of 30 d MACE in patients with acute chest pain was 0.901, which was significantly higher than 0.720 and 0.758 of single detection. Conclusion. The HEART score combined with hs-CRP can better predict the occurrence of 30 d MACE in patients with acute chest pain.